OPTIMALISASI CREATIVE DIGITAL MARKETING UNTUK KEBERLANJUTAN UMKM: PENGGUNAAN GOOGLE BUSINESS DAN WHATSAPP BUSINESS - Amelindha Vania; Nur Laili Fikriah (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
MSMEs in Sawojajar, Malang City, East Java Province are experiencing problems in developing their business, because they are not optimizing digital marketing creatively in marketing their products. With this training, it makes it easier for MSMEs to develop their business not only in the surrounding environment but can be recognized on a national scale. This activity aims to facilitate MSMEs who will develop their product marketing through Google Business and WhatsApp Business, so that MSMEs can use digital media professionally and reliably. With this activity, it is hoped that MSMEs in Sawojajar, Malang City, will be able to sell their products online and expand their market share outside Malang City. The method used in this activity is conducting situation analysis, needs analysis, providing training to MSMEs related to creative digital marketing, evaluating the results of the training, then conclusions and suggestions. The result of this activity is that MSME players have a Google Business account to make it easier to find their business location and can operate sales with Whatsapp Business and know how to increase sales on Whatsapp Business. This activity also provides benefits for lecturers at the State Islamic University (UIN) Maulana Malik Ibrahim Malang as implementers of the activity, so that they can implement the knowledge they have (especially digital marketing knowledge) to the wider community.